2007
DOI: 10.1073/pnas.0705411104
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic inhibitor release and binding from single-enzyme molecules

Abstract: Inhibition kinetics of single-␤-galactosidase molecules with the slow-binding inhibitor D-galactal have been characterized by segregating individual enzyme molecules in an array of 50,000 ultrasmall reaction containers and observing substrate turnover changes with fluorescence microscopy. Inhibited and active states of ␤-galactosidase could be clearly distinguished, and the large array size provided very good statistics. With a pre-steady-state experiment, we demonstrated the stochastic character of inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
134
1
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(138 citation statements)
references
References 25 publications
(35 reference statements)
2
134
1
1
Order By: Relevance
“…The favorable spectroscopic properties of resorufin have been previously harnessed for the production of sensitive in vitro substrates for esterases and glycosidases (Tokutake et al, 1990;Beisson et al, 2000;Coleman et al, 2007), including single-molecule detection (English et al, 2006;Gorris et al, 2007). Indeed, earlier work has highlighted the utility of resorufin b-glycosides for imaging the activity of GHs, including exo-b-galactosidase in yeast (Saccharomyces cerevisiae; Wittrup and Bailey, 1988) and exo-b-glucosidase in animal cells (Hays et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The favorable spectroscopic properties of resorufin have been previously harnessed for the production of sensitive in vitro substrates for esterases and glycosidases (Tokutake et al, 1990;Beisson et al, 2000;Coleman et al, 2007), including single-molecule detection (English et al, 2006;Gorris et al, 2007). Indeed, earlier work has highlighted the utility of resorufin b-glycosides for imaging the activity of GHs, including exo-b-galactosidase in yeast (Saccharomyces cerevisiae; Wittrup and Bailey, 1988) and exo-b-glucosidase in animal cells (Hays et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from single-molecule experiments on a tetrameric enzyme ascertained the textbook model of cooperativity at a single-molecule level showing that ligand binding of the four subunits was not independent from each other: the majority of tetramers showed a one-step jump from no activity to the highest state of activity without observable intermediate states. Moreover, released inhibitors left occasional conformational traces behind causing heterogeneity among protein molecules [59]. So, it is straightforward to presume that complex communication-patterns emerge both inside individual proteins and in their oligomeric complexes.…”
Section: Initial Attempts and Possible Ways To Model Perturbation Wavmentioning
confidence: 99%
“…In the current review we restrict our summary to those, which can be interpreted as propagating conformational changes of proteins. The framework of perturbation waves can be applied to most processes above, and also allows the construction of efficient models to understand the propagation of noise, the fluctuations and diversity of individual cells governing phenotype variations, cellular movement, cell division and other physical rearrangements inside the cells and the threshold between smaller disturbances and larger damages [58,59]. Fig.…”
Section: Initial Attempts and Possible Ways To Model Perturbation Wavmentioning
confidence: 99%
“…Figure 10 shows the resultant electropherogram from a continuous flow assay of the individual β -galactosidase molecules as the inhibitor d -galactal dissociated (Craig et al 2012b ). In a similar study, although not using a CEbased methodology, Walt proposed that the dissociation of bound d -galactal from a given individual β -galactosidase molecule occurred simultaneously at all four subunits (Gorris et al 2007 ). No stepwise increase in activity as inhibitor molecules dissociated one at a time from a given enzyme molecule was noted.…”
Section: Inhibition By D -Galactalmentioning
confidence: 99%
“…In a later study, using fluorescence microscopy, Yeung found that catalytic rate varies over time for individual molecules of lactate dehydrogenase, but not for reactions catalyzed by single metal ions, suggesting that different conformational states might be a cause of the heterogeneity (Tan and Yeung 1997 ). Further studies, using CE (Craig et al 1996 and fluorescence microscopy (Gorris and Walt 2007), have consistently showed, using different enzymes, that catalytic rates vary between different individual molecules and over time for a given molecule. Such heterogeneity is not limited to catalytic rate.…”
Section: Introductionmentioning
confidence: 98%